Effects of hypopressive gymnastics on pelvic organ prolapse: An integrative review (Research, Society and Development, 2020)
Introduction: Hypopressive abdominal gymnastics offers benefits in physiotherapeutic treatment to improve the intra-abdominal pressure of the diaphragm muscle, improve perineal proprioception and tone the pelvic floor muscle in women. Objective: to analyze the effects of hypopressive gymnastics as a resource for physiotherapeutic treatment in the prolapse of pelvic organs in women. Methodology: Characterized as an integrative literature review, through a descriptive and exploratory approach, the PEDro database (Physiotherapy Evidence Database) was used to collect bibliographic data. The inclusion criteria for the research were scientific articles in Portuguese, English and Spanish published between 2009 and 2019, available online, completely and free of charge and as exclusion criteria, repeated articles, without abstract and which were not included. totally accessible or unrelated to the topic studied here. Results and Discussion: Among the effects of hypopressive gymnastics on pelvic organ prolapse, we observed the performance of pelvic floor muscle training (TMAP), which remains the first-line treatment for pelvic floor dysfunction. Final considerations: Hypopressive gymnastics is less effective than pelvic floor muscle training to activate pelvic floor muscles. Need for suggestions for new studies that include other techniques to act in the treatment of pelvic organ prolapse.